High particulate iron(II) content in glacially sourced dusts enhances productivity of a model diatom ... - Shoenfelt, Elizabeth M.; Sun, Jing; Winckler, Gisela; Kaplan, Michael; Borunda, Alejandra; Farrell, Kayla R.; Moreno, Patricio; Gaiero, Diego M.; Recasens, Cristina; Sambrotto, Raymond N.; Bostick, Benjamin C. (Columbia University, 2017)
Little is known about the bioavailability of iron (Fe) in natural dusts and the impact of dust mineralogy on Fe utilization by photosynthetic organisms. Variation in the supply of bioavailable Fe to the ocean has the potential to influence the global carbon cycle by modulating primary production in the Southern Ocean. Much of the dust deposited across the Southern Ocean is sourced from South America, particularly Patagonia, where the waxing and waning of past and present glaciers generate fresh glaciogenic material that contrasts with aged and chemically weathered nonglaciogenic sediments. We show that these two potential sources of modern-day dust are mineralogically distinct, where glaciogenic dust sources contain mostly Fe(II)-rich primary silicate minerals, and nearby nonglaciogenic dust sources contain mostly Fe(III)-rich oxyhydroxide and Fe(III) silicate weathering products. In laboratory culture experiments, Phaeodactylum tricornutum, a well-studied coastal model diatom, grows more rapidly, and with ...